Zakat Computation and Disclosure Practice in Malaysian Islamic Banks - Ariffin, Noraini Mohd; Osman, Ahmad Zamri (Asian Journal of Accounting Perspectives, 2022)
Research aim: The paper aims to examine the current zakat practices of Islamic banking institutions in Malaysia focusing on zakat computation method and disclosure Design/ Methodology/ Approach: The study initially employs content analysis of the annual report. This is later strengthened by semi-structured interviews with relevant bank officers to address the research question. The annual report of 16 Islamic banks and 6 development financial institutions for the year 2020 are used to analyse the current zakat computation method. Research finding: The findings show that the Growth Method is most used in zakat computation. It is also found that some banks, disclosed more zakat information in the Shariah Committee report as well as in the Notes to the Financial Statements. The choice of method to a certain extent is influenced by the challenges facing these institutions. Five of those are deliberated here - window dressing, the implication of zakatable amount upon adhering to some of Bank Negara Malaysia requirements, the different applications and interpretations of the zakat rate, the shareholdings’ issues, and the different distribution practices. Theoretical contribution/ Originality: The study uses Maqasid Shariah as the lens to frame the zakat computation and disclosure issue. In addition, certain BNM requirement has unintended consequences on zakat practices. Practitioner/ Policy implication: Individual Islamic banks should have a clear internal zakat computation framework that is approved by its Shariah Committee to have an accurate zakat computation for Islamic banks. Research limitation: The paper only focuses on the Malaysian setting. Keywords: Zakat, Islamic Banks, Computation, Disclosure Type of article: Research paper JEL Classification: G21, M41, M49, N25